Effect of the Combining Corn Steep Liquor and Urea Pre-treatment on Biodegradation and Hydrolysis of Rice Straw - Ma, Yulin; Chen, Xu; Khan, Muhammad Zahoor; Xiao, Jianxin; Alugongo, Gibson Maswayi; Liu, Shuai; Wang, Jingjun; Cao, Zhijun (Frontiers in Microbiology, 2022)
A novel pretreatment using Corn steep liquor (CSL) and urea was developed to enhance the enzymatic saccharification and degradability of rice straw (RS). We used RS 1) without (Con) or with additives of 2) 5% urea (U), 3) 9% CSL and 2.5% urea (CU) and 4) 9% CSL and 5% urea (C5U). The result showed that the water-soluble carbohydrate (WSC) conversion of RS reached 69.32% after C5U pretreatment. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction analysis (XRD) confirmed that the surface of pretreated RS exposed more cellulose and hemicellulose due to the disruption of resistant structure of lignocellulose. Pretreated RS significantly decreased neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents and increased crude protein (CP) content and microbial colonization, and induction of Carnobacterium and Staphylococcus attachment. We concluded that pretreated of a combination of CSL and urea has the potential to improve the nutritive value of rice straw.